Weed Dynamics and Yield of Wheat in Long Term Soil Fertility Experiment under Rice-Rice-Wheat Cropping System - Khatri, N.; Pandey, B.P.; Yadav, M.; Chaurasia, B.P.; Bista, M.; Kunwar, B. (Journal of Agriculture and Environment, 2020)
Weed dynamics and yield and yield parameters of wheat was studied in long-term soil fertility experiment under rice-rice-wheat system during winter season of 2018-19. The experiment was laid out in randomized complete block design with nine treatments replicated three times. Treatments were applied as: T1- no nutrients added, T2- N added; T3- N and P added; T4- N and K added; T5- N2:P2O5:K2O added at recommended rate for all crops. Similarly, T6- only N added in rice and N2:P2O5:K2O in wheat at recommended rate; T7- half N; T8- half NP of recommended rate for both crops; and T9- farmyard manure @10 t ha-1 for all crops in rotation. The results revealed that the use of Farm Yard Manure @ 10 t ha-1 gave significantly higher yield of 2393 kg ha-1 followed by recommended chemical fertilizer dose of 100:40:30 N:P2O5:K20 kg ha-1 of 2383 kg ha-1. Considerably, lower grain yield was obtained from treatments that did not receive phosphorus. Similarly, application of FYM @10 t ha-1 followed by recommended fertilizer dose recorded higher weed density and dry weed weight with compared to any of N,P2O5 and K2O or all nutrient omitted treatments.